Sistematična analiza PKP ukrepov s področja socialne varnosti - Mišič, Luka (Delavci in delodajalci, 2022)
The article follows a systematic approach to the analysis of anti covid-19 measures in the field of social security that were passed in Slovenia within the so-called anti-corona pieces of legislation. The aim of the article is not to produce yet another overview of ever changing legislative amendments in the field of social security during the epidemic years of 2020 to 2022, but to classify and examine the content of few selected measures according to the basic principles of social security and the basic purpose of social rights. A systematic analysis reveals, on the one hand, the legislator’s need for rapid adaptation to the changing social reality but, on the other hand, often raises doubts about their soundness and possible political motivations behind their adaptation.
Keywords: advantages and incentives; COVID-19; Slovenija; social assistance; social compensations; social protection; social security; socialna varnost; socialna zaščita; socialne pravice; socialno varstvo; zaščitni ukrepi